EMPLOYEE PERFORMANCE REVIEWED FROM THE TRAINING, COMPETENCE AND WORK DISCIPLINE (CASE STUDY AT PT PLN (PERSERO) UP3 SUKOHARJO) - Annisa Nur Khusrohfianti; Sri Hartono; Istiatin Istiatin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to determine and analyze the effect of training, competence and work discipline on the employee performance of PT PLN (Persero) UP3 Sukoharjo. The type of research used is quantitative descriptive. The research population is all employees of PT PLN (Persero) UP3 Sukoharjo, amounted 55 employees and the sample used is taken from the entire population. The sampling technique uses non-probability sampling or the census sampling method. The research data is in the form of primary and secondary data collected through observation, documentation, questionnaires, interviews, and literature study. The data analysis technique used the classical assumption test, multiple linear regression analysis, hypothesis testing (t test) and coefficient of determination test (R2) with the analytical tool SPSS program version 23. The results showed that training, competence and work discipline each had a positive and significant impact on the employee performance of PT PLN (Persero) UP3 Sukoharjo. The test results for the coefficient of determination (R2) obtained an Adjusted R Square value is 0,773 or 77,3% which indicates that the employee performance of PT PLN (Persero) UP3 Sukoharjo can be influenced by training, competency and work discipline variables, while the remaining 22,7% is explained by other variables not included in this study, for example motivation, compensation, job satisfaction, organizational culture, work environment and other variables. Keywords : Employee Performance, Training, Competence, Work Discipline